The Great Labor Discontent, A Review of The Trends to Consider - Montaudon-Tomas, Cynthia M.; Pinto-López, Ingrid N.; Amsler, Anna (Unidad Editorial UPTC, 2023)
This article analyzes some of the current topics in the world of work, especially the Great Labor Discontent and the Great Resignation. The general objective is to present the conditions surrounding the Great Resignation that allow a better understanding of the changes that are taking place in the workplace. The general background and the main characteristics of the great discontent are presented, and the positive effects that these changes are generating are analyzed, as well as emerging movements such as the return of boomerang employees. The study is based on a literature review and stems from the analysis of news, research, and publications of consulting companies, as well as the most relevant publications that have been developed on the subject to date. JEL Codes: J50, J24, J64, J81 Received: 06/01/2023.  Accepted: 06/06/2023.  Published: 19/07/2023.